Hyaluronan preconditioning of monocytes/macrophages affects their angiogenic behavior and regulation of TSG-6 expression in a tumor type-specific manner - Spinelli, Fiorella Mercedes (2019)
Hyaluronan is a glycosaminoglycan normally present in the extracellular matrix in most tissues. Hyaluronan is a crucial player in many processes associated with cancer, such as angiogenesis, invasion and metastasis. However, little has been reported regarding the action of hyaluronan on monocytes/macrophages in tumor angiogenesis and its consequences on tumor development. In the present study, we investigated the effects of hyaluronan of different sizes on human monocytes/macrophages angiogenic behavior in colorectal and breast carcinoma. In vitro, treatment of monocytes/macrophages with lysates and conditioned media from a breast, but not from colorectal, carcinoma cell line plus high molecular weight hyaluronan induced: i) an increased expression of angiogenic factors VEGF, IL‐8, FGF‐2 and MMP‐2, ii) increased endothelial cell migration and iii) a differential expression of hyaluronan‐binding protein TSG‐6. Similar results were observed in monocytes/macrophages derived from breast cancer patients treated with tumor lysates. Besides, macrophages primed with high molecular weight hyaluronan and inoculated in human breast cancer xenograft tumor increased blood vessel formation and diminished TSG‐6 levels. In contrast, the effects triggered by high molecular weight hyaluronan on monocytes/macrophages in breast cancer context were not observed in the context of colorectal carcinoma. Taken together, these results indicate that the effect of high molecular weight hyaluronan as an inductor of the angiogenic behavior of macrophages in breast tumor context is in part consequence of the presence of TSG‐6.